ANALISIS KOMUNIKASI SIMBOLIK DALAM TRADISI REBO WEKASAN - Ulum, Muhammad Saepul (HIKMAH : Jurnal Dakwah Dan Sosial, 2025)
The purpose of this study is to explore and further elaborate the meaning of denotation, connotation, and myth related to Rebo Wekasan symbols in Samarang District, Garut used semiotic analysis method proposed by Roland Barthes. The data collection techniques used include observation, interview, and literature study. The subject of this research is the feast that is served during the traditional celebration and the selection of informants using intentional sampling technique. The symbol of the tradition on the one hand is water, and on the other hand there is “Uyah” or Salt, “dupy”, “leupeut”, and “bugis” which are typical foods of the area. The essence of the Rebo Wekasan tradition is sharing or giving to ward off danger by providing food with certain symbolic meanings such as water symbolizing purity, “Uyah” or salt as a symbol to protect sick people, dupy as a symbol of rejection, leupeut as a symbol of unity, and bugis symbolizing faith. Tujuan penelitian ini adalah untuk menggali dan menguraikan lebih jauh makna denotasi, konotasi, dan mitos terkait simbol Rebo Wekasan di Kecamatan Samarang, Garut dengan menggunakan metode analisis semiotika yang dikemukakan oleh Roland Barthes. Teknik pengumpulan data yang digunakan meliputi observasi, wawancara, dan studi pustaka. Subyek penelitian ini adalah hari raya yang dihidangkan pada saat perayaan adat dan pemilihan informannya menggunakan teknik sampling intensional. Simbol dari tradisi tersebut di satu sisi adalah air putih, dan di sisi lain ada “Uyah”atau Garam, “dupy”, “leupeut”, dan “bugis” yang merupakan makanan khas daerah tersebut. Inti dari tradisi Rebo Wekasan adalah berbagi atau memberi untuk menangkal mara bahaya dengan cara menyediakan santapan dengan makna simbolik tertentu seperti air melambangkan kesucian, “Uyah” atau garam sebagai sombol untuk melindungi orang yang sakit, dupy sebagai simbol penolakan, leupeut sebagai simbol persatuan, dan bugis melambangkan keimanan.